STUDY OF THE ROLE OF THE CREDIT AND BANKING SYSTEM IN THE MODERNIZATION OF THE ECONOMY OF UKRAINE (1861 - 1917): CONTEMPORARY HISTORICAL, ECONOMIC AND LEGAL VIEWS - Михайлюк, Віталій (SWorldJournal, 2023)
The article reviews the scientific works of researchers on the history of the formation of domestic banking in the second half of the 19th century and in the first two decades of the 20th century. It was the time of the transition of Ukrainian society to